Conductivity and structural analysis of perovskite-like BiAlO3 doped (K0.44Na0.52Li0.4)(Nb0.86Ta0.1Sb0.04)O3 based perovskites system. Issue 1 (25th January 2023) - Kumari, Poonam; Deeksha,; Nanda, Dipika; Thakur, Shweta; Kumari, Shilpa; Singh, Anupinder; Rai, Radheshyam
Abstract: In this study, the structural analysis of the samples (1-x)(K0.44 Na0.52 Li0.04 -Nb0.86 Ta0.1 Sb0.04 )-x(BiAlO3 ) (x = 0, 0.005, 0.007, 0.01, and 0.05) showed that the samples have orthorhombic and tetragonal phases. The effect of increasing concentration of BA in (1-x)(K0.44 Na0.52 Li0.04 -Nb0.86 Ta0.1 Sb0.04 )-x(BiAlO3 ) samples have been studied on impedance and modulus analysis of the samples in 100 °C–500 °C temperature range. All the samples were found to exhibit NTCR behavior. AC conductivity showed that the conduction increase with increase in temperature. The dielectric and capacitive behavior of the samples were also analyzed from the dielectric and modulus study of the samples.